Individual macular layer evaluation with spectral domain optical coherence tomography in normal and glaucomatous eyes - Fujihara, Fernanda Mari Fagundes (2020)
Purpose: To evaluate differences in the thickness of the individual macular layers between early, moderate, and severe glaucomatous eyes and compare them with healthy controls. Patients and Methods: Subjects with glaucoma presenting typical optic nerve head findings, high intraocular pressure with or without visual field (VF) damage and normal controls were included. All participants underwent 24–2 perimetry and spectral-domain OCT. Patients were divided into three groups (early, moderate, and severe) based on the mean deviation of the VF and a healthy control group. The device segmented the layers automatically, and their measurements were plotted using the means of the sectors of the inner (3mm) and outer (6mm) circles of the ETDRS grid. Results: A total of 109 eyes qualified for the study: 14 in the control group and 52, 18 and 25 in the early, moderate and severe groups, respectively. Mean age was 66.13 (SD=12.38). The mean thickness of the circumpapillary retinal nerve fiber layer (RNFL), total macular thickness (TMT), macular RNFL, ganglion cell layer (GCL) and inner plexiform layer (IPL) were significantly different between the 4 groups, with progressive decrease in thickness. Significant overall difference was found for the inner nuclear layer (INL), and the severe glaucoma group presented thicker measurements than controls and early glaucoma. Outer nuclear layer (ONL) was thinner in severe glaucoma group compared with early glaucoma group. Conclusion: Individual macular layer measurement using the inner and outer circles of the ETDRS grid is useful to evaluate different stages of glaucoma. The INL thickening and ONL thinning in advanced glaucoma should be explored in the future studies.